2019
DOI: 10.22515/shirkah.v3i3.194
|View full text |Cite
|
Sign up to set email alerts
|

Generation XYZ’s Perception on Zakat Mal and Tax: The Planned Behavior Perspective

Abstract: The research aims to apply the theory of planned behavior to predict respondents’ intention of offering zakat mal (wealth) and tax payment. The research brings questionnaires, aiming to generate a descriptive research. Technique of analysis being applied is the Partial Least Square (PLS) with SmartPLS software. The descriptive statistics shows that respondents have deep understanding between zakat mal and tax. In addition, the analysis using PLS reveals that attitude, subjective norm, and behavioral control in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 3 publications
2
8
2
Order By: Relevance
“…Zakat intention is a person's personal view of the tendency to bring up a behavior. It includes motivational factors that indicate how hard the effort is and how much effort the person concerned uses to display behavior [24].…”
Section: Management Information Systems On Integrated Student and Lec...mentioning
confidence: 99%
“…Zakat intention is a person's personal view of the tendency to bring up a behavior. It includes motivational factors that indicate how hard the effort is and how much effort the person concerned uses to display behavior [24].…”
Section: Management Information Systems On Integrated Student and Lec...mentioning
confidence: 99%
“…However, in 2018 OPZ realized online zakat to increase zakat income from the millennial generation, it still cannot be maximized. This fact is evidenced in Saragih's (2018) research showing that the millennial generation (generation Y) trusts zakat more directly to mustahik rather than giving it to OPZ. Saragih (2018) mentions why muzakki who directly choose zakat are because they feel more affectionate than giving it to OPZ.…”
Section: Introductionmentioning
confidence: 99%
“…This fact is evidenced in Saragih's (2018) research showing that the millennial generation (generation Y) trusts zakat more directly to mustahik rather than giving it to OPZ. Saragih (2018) mentions why muzakki who directly choose zakat are because they feel more affectionate than giving it to OPZ. Furthermore, they do not need to pay additional fees, they already know the actual condition of the mustahik, and finally, there are still many mustahics that BAZ / LAZ has not reached.…”
Section: Introductionmentioning
confidence: 99%
“…This is also supported by research conducted by Pratiwi (2018) who found in her research that behavioral control had a. significant effect on compliance behavior in paying zakat. H4: Behavioral control has a positive and significant effect on willingness to pay Zakat According to the theory of planned behavior intention is a direct reference of behavior, where behavior can be directly influenced by behavioral intentions, this is also supported by researcher Saragih (2018) found that intention has a positive and significant effect on their compliance in paying zakat. Pratiwi (2018) found in his research that intention has a significant effect on compliance behavior in paying zakat.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Several studies on subjective norms affecting muzakki intentions have been carried out by several researchers including Nuryana (2016) in his research said that subjective norms have a significant influence on muzakki compliance intentions in paying professional zakat. Saragih (2018) in his research found that subjective norms have a significant influence on muzakki's intentions in paying zakat. Pratiwi (2018) found in her research that subjective norms have a significant influence on the intention to pay zakat.…”
Section: Literature Reviewmentioning
confidence: 98%